An analysis of the structure and maturity of the Doha property market - Makanya, Rufaro (Department of Construction Economics and Management, 2018)
This research is primarily focussed on the dynamics that determine the maturity of property markets. It considers the evolving institutional environment in which markets function and highlights the characteristics of property markets in both developed and developing countries in order to analyse the characteristics required to determine their maturity. The primary research targets the city of Doha located in Qatar. This is compared to other property markets around the world, using the available literature and the knowledge of Doha's expatriate property professionals. The purpose of this research is to contribute to the research and knowledge of property markets by assessing the players, institutions and characteristics of the property market in Doha to assess whether it is driven by the same maturity forces as those that drive typical markets elsewhere. The research concludes that property market outcomes could be improved in Doha by improving and developing the property market maturity factors. Considering all the factors. The property market in Doha was identified as fairly immature in comparison to international best practice. It has improved significantly recently and is on a path to compete with the more mature markets in future. Recommendations proposed in the research findings focused particularly around the strengthening of property market institutions to allow for further improvements to market maturity and cautioned against verbatim copying of successful market practices from elsewhere.